Effect of temperature and transport on the yield and composition of pyrolysis-derived bio-oil from glucose - Ansari, Khursheed Badruddin (2018)
The fast pyrolysis of biomass forms bio-oil, char, and light noncondensable gases. Bio-oil is the desired product in context of converting biomass to biofuel. The effect of temperature on bio-oil yield and composition is anticipated to be different under reaction-limited and transport-limited operating conditions. Attaining fundamental understanding of the effect of temperature and transport on bio-oil yield and composition is challenging, because of limited knowledge of pyrolysis chemistry and the inter-relationship between chemistry and transport. In this work, we performed thin-film and powder pyrolysis experiments to investigate the thermal decomposition of glucose (biomass model compound) under both reaction-controlled and transport-limited operating conditions. In thin-film (size ≤10 μm) experiments, the effect of temperature on pyrolysis product distribution, especially on bio-oil yield and composition, was studied. In addition, using the thin-film data, mechanistic insights into glucose decomposition were provided and a map of reaction pathways was proposed. Decomposition of glucose in the reaction-controlled regime is initiated by dehydration reactions. With increase in temperature, anhydrosugars (viz, levoglucosan and levoglucosenone) apparently converted to furans (hydroxymethylfurfural) and light oxygenates (formic acid/methyl glyoxal), respectively, as ring opening and fragmentation reactions became more facile. Pyrans remained relatively stable. The effect of transport was investigated by performing pyrolysis experiments with different particle sizes. The variation in the yield and composition of bio-oil, with respect to temperature and particle size, was also analyzed. In the case of glucose powder, levoglucosan yield increased significantly with particle size but decreased marginally with temperature, while hydroxymethylfurfural, furfural, formic acid, and methyl glyoxal yields monotonically increased as the temperature and particle size each increased. A thin film of glucose gave a lower yield of bio-oil and a higher yield of char than that of glucose powder.